Keterampilan Konselor Dalam Mengembangkan Manajemen Bimbingan Konseling Di Sekolah - Isra, Fauzi (IJoCE: Indonesian Journal of Counseling and Education, 2020)
Teacher guidance and counseling must have a strong foundation science, because the counselor is one of the types of education personnel in the law of the Republic of Indonesia number 20 of 2003. In line with the recognition of government policy counselor in developing the quality of teacher guidance and counseling. Counseling skill are seen as the minimum skills a professional counselor should have mastery of counseling skills is an important aspect for the continuity of the counseling process. The performance of the counselor is the result of the work of the counselor as a professional who has special expertise and experience in the field of counseling who has duties and responsibilities, namely providing services to students according to their needs and helping students develop themselves optimally. There are still many people who think that guidance and counseling work can be done by anyone. As long as they are able to communicate and interview. This assumption says that guidance and counseling services are solely directed at providing assistance with regard to problem solving efforts in a narrow sense. This counseling service is not solely directed at solving problems, but includes various types of services and support activities so that new functions can be realized. As a formal institution, schools are responsible for educating and preparing students to successfully adapt to society and be able to solve various problems it faces.